Effects of threat, trait anxiety and state anxiety on police officers' actions during an arrest - Renden, Peter G. (Legal and criminological psychology, 2017)
Purpose. We investigated the effects of threat and trait anxiety on state anxiety and how that affects police officers’ actions during an arrest. Most experiments on police performance under anxiety test the performance of one particular skill. Yet, police work often involves concerted use of a combination of skills. Methods. We created situations – with two different levels of threat – in which officers had to choose and initiate their actions to control and arrest a non-cooperative suspect. We examined whether threat, trait anxiety and state anxiety influenced decision-making (e.g., choosing the appropriate actions) and performance (e.g., quality of communication and the execution of skills). Results. Trait anxiety affected the level of state anxiety, but not any of the decision-making and performance variables. As for decision-making, results showed that only threat determined which action officers took to gain control over the suspect. As for performance, higher levels of state anxiety were accompanied by lower scores of overall performance, communication, proportionality of applied force and quality of skill execution. Conclusion. It is concluded that state anxiety not only impairs performance of single perceptual-motor tasks, but also relevant accompanying skills such as communicating and applying appropriate force. We argue that police training should focus on an integrated set of decision-making and perceptual-motor skills and not just on the performance of isolated motor skills.